Ethno-Medicine Practiced by Magar People in Tahoon Palpa, Nepal (ZOO-Journal, 2019)
The present research work seeks to explore ethno-medicinal plants and animals used by the Magar people in Tahoon Palpa for primary healthcare. A total of 48 medicinal plant species belonging to 34 families and 48 genera, and 10 animal species belonging to 10 families and eight orders, have been recorded from the study area. The most dominant families of plants belonged to Eurphorbiaceae, Gramineae, Leguminosae and Liliaceae (3 species in each). The main medicinal plant species were Adhatoda vasica (Nees), Cannabis sativa (Linnaeus), Artimisia vulgaris (Linnaeus), Terminalia chebula (Retz), Terminalia bellirica (Roxb), Phyllanthus emblica (Linnaeus), Ocimum sanctum (Linnaeus), Bauhinia variegate (Linnaeus), Mentha spicata (Linnaeus), Zanthoxylum armatum (DC.), Acorus calmus (Linnaeus), Euphorbia hirta (Linnaeus), Azadirachta indica (A. Juss), etc. while animal species were Achaearanea tepidariorum (C.L. Koch), Potamon fluviatile (Herbst), Passer domesticus (Linnaeus), Canis aureus (Linnaeus), Apis cerena (Fabricius), Limax flavus (Linnaeus) etc. In the study area the local people mostly use plant species to treat cuts, wounds, stomach problem, cough, fever, dysentery etc., while animal products were used for typhoid, bone fracture, intestinal problems, piles, rheumatism, cough etc. This paper recommends to the implementation of conservation activities such as awareness to the locals, appropriate management and initiating scientific research to ensure a minimum viable population of the medicinal flora and fauna.